Psychological consequences of limb amputation: literature review - Rudenko Єлизавета; Assonov Дмитро (Psychosomatic Medicine and General Practice, 2023)
This work contains a literary review, which systematizes the knowledge about psychological consequences of limb amputation, the pathopsychological characteristics of people who had limb amputations and comorbid symptoms of mental disorders. We conducted a literary analysis on the topic under study, which includes sources published in the last 5 years. PubMed, Google Scholar and Cochrane Library databases were analyzed. From 96 analyzed sources we included 28 that reached our inclusion criteria. Overall, psychological distress experienced by people after limb amputation is a very relevant and underestimated problem in the medical community. Significant criterion in the context of the research topic is also the clinical and psychological characteristics of individuals, which has a significant impact on the specifics of the psychological consequences of amputation. Thus, the emergence of negative psychological consequences and mental disorders after amputation is due to the characteristics of the premorbid personality, such as certain psychological personality traits, coping strategies, comorbid mental and somatic diseases. The age of the amputees, the availability of social support, as well as the reasons, type and level of amputation were also mentioned as important factors. Distorted perception of the body scheme, social stigma and negative emotional reactions are also the direct psychological consequences of amputation in the studied category of persons. The most common mental disorders include PTSD, anxiety, depression, and substance use disorder. Among the somatic symptoms of amputation, attention should be paid to the consequences of functional limitations, sexual dysfunctions and phantom pain.